Do khan aik pakistan, Sooba sarhad ki pakistan m shamoliat - DR MA , SOOFI (Times publications , Lahore, 2003)
A visually engaging guide by Rupert Matthews that presents key events and figures in history through detailed timelines for easy reference and understanding.